The Impact of High Ultra-Processed Food Consumption on Obesity Risk among Young Adults - Anisa Putri; Wei Zhang (Media of Health Research, 2025)
Ultra-processed foods (UPFs) are industrial formulations characterized by high levels of added sugar, fat, sodium, and food additives, and have become a dominant component of modern diets. Recent evidence suggests that increased UPF consumption is strongly linked to obesity and other metabolic disorders. This study aims to investigate the impact of high UPF consumption on obesity risk among young adults. A cross-sectional study was conducted involving 320 participants aged 18–30 years in Yogyakarta, Indonesia, and Shanghai, China. Dietary intake was assessed using a validated food frequency questionnaire and categorized based on the NOVA classification system. Body mass index (BMI) was measured and obesity was defined according to WHO standards. Logistic regression analysis was applied to examine the association between UPF consumption and obesity risk. The findings revealed that individuals with the highest tertile of UPF consumption had a 2.6-fold increased risk of obesity compared to those in the lowest tertile (OR=2.63; 95% CI: 1.55–4.47, p<0.01). Frequent consumption of sugar-sweetened beverages and packaged snacks were the strongest predictors of obesity. These results emphasize the urgent need for dietary interventions and public health strategies to reduce UPF consumption among young adults. This research contributes to existing evidence by providing cross-country data from Indonesia and China, highlighting the global relevance of dietary patterns and obesity prevention strategies.